DEVELOPMENT OF AN EXTENDED-RANGE BONNER SPHERE SPECTROMETER FOR CHINA INITIATIVE ACCELERATOR-DRIVEN SYSTEM. Issue 2 (9th December 2022) - Wen, Z W; Song, S Y; Xu, J K; Gong, Y W; Huang, Y X; Ran, J L; Tang, X Q; Chen, Z Q; Li, Y; Luo, P
Abstract: To measure the extended-range neutron spectra and calibrate the extended-range neutron dosemeters of the China initiative Accelerator-Driven System (CiADS), an Extended-range Bonner Sphere Spectrometer (EBSS) has been developed. The EBSS was designed based on the PHITS codes, investigating various combinations of materials and diameters of the neutron moderators and the neutron multipliers for extended-range neutrons. Finally, seven polyethylene-only spheres and seven extended-range spheres were selected and subsequently built. The neutron multipliers of the extended-range spheres embedded concentric shells of lead, copper and tungsten. The response functions of the EBSS were analyzed and experimentally validated. It was subsequently tested with 252 Cf neutron source and cosmic ray neutron source. The results demonstrate that the EBSS is capable of accurately measuring neutron spectra.